Effects of Branched-chain Amino Acids on In vitro Ruminal Fermentation of Wheat Straw - Zhang, Hui Ling (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
This study investigates the effects of three branched-chain amino acids (BCAA; valine, leucine, and isoleucine) on the in vitro ruminal fermentation of wheat straw using batch cultures of mixed ruminal microorganisms. BCAA were added to the buffered ruminal fluid at a concentration of 0, 2, 4, 7, or 10 mmol/L. After 72 h of anaerobic incubation, pH, volatile fatty acids (VFA), and ammonia nitrogen (NH(3)-N) in the ruminal fluid were determined. Dry matter (DM) and neutral detergent fiber (NDF) degradability were calculated after determining the DM and NDF in the original material and in the residue after incubation. The addition of valine, leucine, or isoleucine increased the total VFA yields (p≤0.001). However, the total VFA yields did not increase with the increase of BCAA supplement level. Total branched-chain VFA yields linearly increased as the supplemental amount of BCAA increased (p<0.001). The molar proportions of acetate and propionate decreased, whereas that of butyrate increased with the addition of valine and isoleucine (p<0.05). Moreover, the proportions of propionate and butyrate decreased (p<0.01) with the addition of leucine. Meanwhile, the molar proportions of isobutyrate were increased and linearly decreased (p<0.001) by valine and leucine, respectively. The addition of leucine or isoleucine resulted in a linear (p<0.001) increase in the molar proportions of isovalerate. The degradability of NDF achieved the maximum when valine or isoleucine was added at 2 mmol/L. The results suggest that low concentrations of BCAA (2 mmol/L) allow more efficient regulation of ruminal fermentation in vitro, as indicated by higher VFA yield and NDF degradability. Therefore, the optimum initial dose of BCAA for in vitro ruminal fermentation is 2 mmol/L.